PENGARUH JENIS ASAM ALAMI TERHADAP PENURUNAN KADAR LOGAM BERAT TIMBAL DALAM DAGING IKAN TERI (Stelophorus indicus Sp) ASAL TELUK PALU - Yulita Nelin Sipa; Jamaluddin Jamaluddin; Ihwan Ihwan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
Research on the effect of type natural acid against decline of content heavy metals plumbum in meat anchovy (Stelophorus indicus Sp) origin bay Palu. The purpose of this study was to determine the best type of acid used in dissolving levels of plumbum as heavy metals for 1 hour immersion and to determine the number of levels of heavy metals of lead that can be dissolved during immersion 1 hour. This study begins with a sample digestion using nitric acid, further qualitative test reagents dithizon 0.005% (positive), potassium iodide (positive) and sodium carbonate (postitif). Qualitative results test that showed a positive result then measured in metal content of plumbum using atomic absorption spectrophotometer (AAS) at λ 283.3 nm. Then soaking using tamarind are 5%, acetic acid 10%, the filtrate pineapple 100%, starfruit 100% and lime 25% for 1 hour at room temperature, after measuring the metal content of plumbum with atomic absorption spectrophotometer (AAS) in λ 283.3. The results show levels of heavy metals plumbum before immersion average of 0.8 mg/kg, the average concentration of heavy metals plumbum after soaking tamarind 5% amounting to 0.787 mg/kg (1.64%), 10% acetic acid at 0.789 mg/kg (1.39%), pineapple filtrate 100% of 0.7882 mg/kg (1.49%), starfruit 100% 0.789 mg/kg (1.39%) and lime 25% of 0.7916 mg/kg (1.06%). Thus tamarind 5% is the best type of acid to reduce levels of plumbum metal in Palu bay anchovy origin.Keywords: Acid, Anchovy (Stelophorus indicus Sp), Content, Plumbum